Analysis of strategies to counter hybrid threats, including disinformation and economic pressure - Kalenyk, A. O.; Каленик, А. О. (Актуальні питання розвитку сектору безпеки і оборони (зарубіжний досвід) : зб. тез доп. учасників ХХVІ Міжнар. наук.-практ. конф. інозем. мовами для здобувачів освіти (м. Вінниця, 4 квіт. 2025 р.). – Вінниця : ХНУВС, 2025. – С. 106-107, 2025)
Стверджено, що аналіз стратегій протидії гібридним загрозам потребує комплексного підходу. Необхідно враховувати всі аспекти, включаючи дезінформацію, економічний тиск та кіберзагрози. Тільки спільними зусиллями можна ефективно протистояти цим викликам та забезпечити безпеку держави та суспільства.

It is argued that the analysis of strategies to counter hybrid threats requires a comprehensive approach. It is necessary to take into account all aspects, including disinformation, economic pressure and cyber threats. Only through joint efforts can these challenges be effectively confronted and the security of the state and society be ensured.
Keywords: гібридні загрози; протидія гібридним загрозам; дезінформація; економічний тиск; кібербезпека; hybrid threats; countering hybrid threats; disinformation; economic pressure; cybersecurity